2020
DOI: 10.36812/pag.2020261201-221
|View full text |Cite
|
Sign up to set email alerts
|

Sabor, história e economia local: percepções dos consumidores gaúchos sobre o Queijo Colonial

Abstract: Os queijos artesanais podem ser considerados patrimônios das comunidades que os produzem, pois expressam a evolução de um conhecimento compartilhado ao longo do tempo. O consumo desses queijos envolve a valorização de atributos tangíveis, como sabor, e características intangíveis, como tipicidade, sustentabilidade ambiental, social e econômica. O Queijo Colonial do Rio Grande do Sul é produzido por comunidades de descendentes de imigrantes, especialmente italianos e alemães, desde meados do século 19. O volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
0
18
0
2
Order By: Relevance
“…Consumers of Canastra cheeses mentioned “happiness” and “pleasure” of eating in home use tests, which decayed through the home storage, meanwhile expressions of unsatisfaction and disappointment were more used by the end of the home test period (Rodrigues et al, 2021). Colonial cheese has a positive reputation, presenting high cost–benefit ratio and following hygiene standards, which meet the emotional and functional needs of consumption (Ambrosini et al, 2020). Using free word association, Ziemann, Berreta, and Sant'Anna (2022) observed that handcraft cheeses evoked as many positive feelings/attitudes as those sanitary inspected ones, although the non‐inspected were highly related to sensory aspects such as “delicious” and “aroma,” meanwhile inspected cheese evoked such as “industrialized,” “safety,” “quality,” “hygiene.” In these contexts, taste is a critical aspect on food acceptance, and expectation, like showed previously by Ziemann et al (2022), may affect perceived flavor.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumers of Canastra cheeses mentioned “happiness” and “pleasure” of eating in home use tests, which decayed through the home storage, meanwhile expressions of unsatisfaction and disappointment were more used by the end of the home test period (Rodrigues et al, 2021). Colonial cheese has a positive reputation, presenting high cost–benefit ratio and following hygiene standards, which meet the emotional and functional needs of consumption (Ambrosini et al, 2020). Using free word association, Ziemann, Berreta, and Sant'Anna (2022) observed that handcraft cheeses evoked as many positive feelings/attitudes as those sanitary inspected ones, although the non‐inspected were highly related to sensory aspects such as “delicious” and “aroma,” meanwhile inspected cheese evoked such as “industrialized,” “safety,” “quality,” “hygiene.” In these contexts, taste is a critical aspect on food acceptance, and expectation, like showed previously by Ziemann et al (2022), may affect perceived flavor.…”
Section: Resultsmentioning
confidence: 99%
“…Schouteten et al (2015) also observed that health‐related labels might emotionally profiles of cheese products. Colonial cheese consumers have related consumption of the product to pleasure, satisfied, happiness, nostalgia, joy and quietness (Ambrosini, Kroeff, Matte, Cruz, & Waquil, 2020). To assess consumers' emotions and aiming at the use of a more universal language, the study of emotions has been using emojis, which are graphic characters used to convey ideas, attitudes, moods and emotions, in addition to partially replacing written language.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As famílias que produziam leite exclusivamente para autoconsumo foram responsáveis pela produção de 90,09% da quantidade total de queijos em 2017, ante 43,26% em 2002, revelando que a intensificação da produção comercial de leite foi acompanhada pela desativação (menos famílias produzindo) e desintensificação (redução da quantidade produzida) da agroindustrialização de leite. Ainda em relação aos sistemas produtivos, cabe destacar que não foram observados: a) processos de transição agroecológica nessa atividade, ou mesmo intensificação do uso de tecnologias na perspectiva da produção orgânica de leite (Capellesso & Cazella, 2015;Balem & Machado, 2019;Balem et al, 2020;Gazolla & Lovatel, 2020); b) tampouco a perspectiva da constituição de sistemas agroalimentares localizados (Ceolin, Silva & Ambrosini, 2020;Ambrosini et al, 2020); nem, por fim, c) avanços na produção leiteira com uso de estratégias de agregação de valor utilizando mecanismos de indicação geográfica (Niederle, 2013). Em sentido inverso, observou-se ampla integração dos produtores de leite que se mantiveram na atividade comercial às cadeias nacionais e globais de valor, com avanço nas formas empresariais de agricultura, conforme tendência apontada por Ploeg (2008).…”
Section: Transformações Nos Sistemas Produtivos E O Destino Da Produçãounclassified
“…O Brasil ocupa, atualmente, a sexta posição do índice de maiores produtores de queijo do mundo (ZAFFARI, 2018), com uma produção de 1,2 milhões de toneladas ao ano, gerando uma movimentação de 22 bilhões de reais no país (SOARES; RODRIGUES, 2019). O volume anual de queijo colonial produzido no estado do Rio Grande do Sul é em torno de 12,5 mil toneladas, sendo a maior parte processada artesanalmente (AMBROSINI et al, 2020).…”
unclassified